Ensino Língua Portuguesa para surdos no Estado Novo: por uma história das Ideias Linguísticas - Baalbaki, Angela Corrêa Ferreira (Linguarum Arena, 2019)
The present article aims to analyze teaching manuals produced by teachers of the National Institute of the Deaf (INES) in Brazil during the period called Estado Novo. At that time, a nationalistic linguistic policy strongly affected speakers of other languages (mainly immigrants). We have based our analyses, above all, on the theoretical proposal of the History of Linguistic Ideas, focusing on the production of manuals (Puech, 1998) of oral language teaching for deaf students. The period is large-scale marked by the nationalism to be built around the national language, namely Portuguese, and by the elaborated and educated Brazilian voice cult. The nationalist proposal would not be outside the school for the deaf. Its methodology would be embodied in the oral view. However, we can observe that the presence of a methodology based on the use of signals was not denied by the book authors; being considered, however, adequate for those deaf considered “deprived intelligence” or out of conditions for learning oral language. Thus, a deaf Brazilian identity was created (Witchs, 2014): a deaf person who spoke the national language and was able to sustain herself/himself with the strength of her/his own work.